PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH STUDI EMPIRIS KABUPATEN DAN KOTA SE-EKS KARESIDENAN PEKALONGAN PERIODE 2016-2020 - Ika Novita Ardelia; Hilda Kumala Wulandari; Yenny Ernitawati; Dumadi Dumadi (Jurnal Aplikasi Akuntansi, 2022)
Since the enactment of the law on regional autonomy, every local government is required to manage finances. Every year, transparency and responsibility are paramount. Good financial management is proven to greatly affect the financial performance of a region. Therefore, this study examines and analyzes the impact of financial performance on local revenues, capital expenditures, and balancing funds. This is done through an empirical approach with secondary data collected from the City and Regency of the former Pekalongan Residency for the 2016-2020 period in the form of the APBD realization financial report used as a secondary data sample in this study using the saturated sampling method. The results of this study indicate that the first local revenue has an effect on the financial performance of local governments. Second, this study reveals that capital expenditure does not have a significant impact on the financial performance of local governments. Third, balancing funds have a significant effect on the financial performance of local governments. Finally, it was found that the simultaneous influence of regional original income, capital expenditure, and balancing funds was significant on the financial performance of local governments.